367 A phase 1/1b dose-escalation study of intravenously administered SB 11285 alone and in combination with atezolizumab in patients with advanced solid tumors. (9th November 2020) - Luke, Jason; Janku, Filip; Olszanski, Anthony; Leach, Kevin; Iyer, Radhakrishnan; Abbas, Atif
Abstract : Background: Activation of the Stimulator of Interferon Genes (STING) pathway within immune and tumor cells of the tumor microenvironment (TME) results in durable anti-tumor effects via induction of innate and adaptive immunity. SB 11285 is a next-generation immunotherapeutic cyclic dinucleotide that activates the STING pathway leading to stimulation of tumor-resident APCs, NK cells and priming of tumor antigen specific CD8+ T cells. In preclinical studies using multiple tumor-derived cell lines, SB 11285 induced cytokines, such as IFN-α and -β, TNF- α and others consistent with engagement of TBK1 downstream of STING activation. Exposure of SB 11285 directly to tumor also induces cell death by STING-mediated apoptosis. SB 11285 reduced tumor volumes in multiple rodent tumor models when administered intravenously, intraperitoneally or intratumorally, as monotherapy and with amplified effect in combination with CTLA-4 or PD-1 antibodies. The novel properties of SB 11285 facilitate systemic administration which may facilitate trafficking of newly activated CD8+ T cells from the periphery into the TME. Methods: This open-label, multicenter phase 1/1b clinical trial (NCT04096638 ) will enroll approximately 110 patients in the dose escalation (Part 1) and expansion cohorts (Part 2). Part 1 will includ parallel dose escalations evaluating ascending doses of intravenously administered SB 11285 via 3+3 design with respect to dose-limiting toxicities, maximum tolerated dose, recommended phase 2 dose (RP2D) and the pharmacokinetic/pharmacodynamic profile. Part 2 Expansion Cohorts of the study will explore initial efficacy via overall response rate in pre-specified tumor types (such as Melanoma, Head and Neck Squamous Cell Carcinoma) at the RP2D in combination with atezolizumab. SB 11285 will be administered as monotherapy weekly on Days 1, 8, 15, and 22 of repeated 28-day cycles in escalating doses and in combination with atezolizumab administered Q4W. Biological effects of SB 11285 will be evaluated via changes in immune cell types, serum cytokines, and gene expression patterns indicative of activation of the peripheral and TME immune compartments. Results: 'N/A' Conclusions: 'N/A'